2017
DOI: 10.18203/2394-6040.ijcmph20173366
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice study on cardiopulmonary resuscitation among medical and nursing interns

Abstract: Background: Cardiac arrest is a substantial public health problem estimated to account for 15–20% of all death. It is documented that a timely performed cardiopulmonary resuscitation (CPR) can largely prevent sudden death. Being important members of the health care delivery team, medical professionals and nursing staff are deemed to pass the basic skills and expertise which are needed to perform CPR. The principle objectives of the research project are to assess knowledge and attitude of CPR and to compare kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
1
13
1
Order By: Relevance
“… 3 , 4 A study conducted in India among medical and nursing interns showed that 36% of nursing interns and 46% of medical interns had poor knowledge and 42% of medical interns and 52% of nursing interns poor practices. 5 Almost all participants (99%) had positive attitudes toward CPR. 5 Another study conducted in Spain showed that 64.7% of hospital staff had attended at least one CPR course and 7% of nursing staff had not had CPR training to American Heart Association standards.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“… 3 , 4 A study conducted in India among medical and nursing interns showed that 36% of nursing interns and 46% of medical interns had poor knowledge and 42% of medical interns and 52% of nursing interns poor practices. 5 Almost all participants (99%) had positive attitudes toward CPR. 5 Another study conducted in Spain showed that 64.7% of hospital staff had attended at least one CPR course and 7% of nursing staff had not had CPR training to American Heart Association standards.…”
Section: Introductionmentioning
confidence: 95%
“… 5 Almost all participants (99%) had positive attitudes toward CPR. 5 Another study conducted in Spain showed that 64.7% of hospital staff had attended at least one CPR course and 7% of nursing staff had not had CPR training to American Heart Association standards. 6 A study conducted in India indicated that 17.6% of dental interns and 13% of dental postgraduate students had poor knowledge of CPR.…”
Section: Introductionmentioning
confidence: 95%
“…However, improving quality of care provided for patients experience cardiac arrest utilizing current knowledge and practice is needed to improve the CPR outcomes among patients [18]. In fact, the ability of nurses and the other health care professionals to deal with cardiac arrest effectively depends largely on their knowledge and training regarding the CPR procedure [19].…”
Section: Introductionmentioning
confidence: 99%
“…Poormirza et al [24] reported that CPR procedure is the most important life-saving skill for registered nurses. Besides, adequate knowledge and skills regarding CPR among critical care nurses and other health care providers is essential to increase the chance of survival and to avoid the post CPR complications [19]. According to Gempeler [25], having adequate CPR knowledge among the trained healthcare professionals is essential to perform CPR immediately and effectively, and to improve survival of patients who experience cardiac arrest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation